Écologie et régulation des relations homme-faune : repenser la conservation de la biodiversité par les Communs - Nicolas Gaidet; Sigrid Aubert (VertigO)
The way in which Man thinks and represents his relations with wild animals has been deeply marked, first, by the way ecologists have described, organised and explained the living world, and second, by the way jurists have developed and interpreted the law. The modes of classification, quantification and functionalisation of life established by ecological science have contributed to the formulation of the law around objective categories participating in an anthropocentric goal of regulating human-nature relations. This regulation mainly consisted in mitigating the impacts of economic development and preserving a minimum biodiversity. In this story, the place and role of wild animals as actors of natural systems have been forgotten. We propose here to question the structure of the law by confronting it with the options opened up by the renewal of ecological sciences, debates and public policy mechanisms in order to go beyond the reductive and anthropocentric vision of the challenge of biodiversity erosion. The approach by the Communes today contributes to questioning the dominant models of regulation of human societies by favouring "common action". We analyze the perspectives offered by this approach to restore the notions of interdependence, responsibility, and solidarity between humans and non-humans in the use of resources.